PENGARUH MODEL PEMBELAJARAN ECOLITERACY AND ADAPTATION (ELA) BERBASIS KEARIFAN LOKAL TERHADAP PENINGKATAN MINAT BELAJAR IPAS PADA SISWA KELAS 5 SD NEGERI GEDONGKUNING - Ramadhan, Diky; Hermawan wahyu Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students’ learning interest in Natural and Social Sciences (IPAS) is still relatively low, which affects their motivation and learning outcomes. This study aims to determine the effect of the Ecoliteracy and Adaptation (ELA) learning model based on local wisdom on improving the learning interest of fifth-grade students at SD Negeri Gedongkuning. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The subjects consisted of two classes, namely an experimental class that applied the Ecoliteracy and Adaptation (ELA) model and a control class that used the Problem-Based Learning (PBL) model. Data were collected through observation and documentation, while data analysis was conducted using prerequisite tests (normality and homogeneity) and hypothesis testing with an Independent Samples t-test using SPSS. The results showed that students’ learning interest in the experimental class increased significantly, as indicated by the increase in average scores from pretest to posttest and supported by statistical analysis showing a significance value of 0.000 < 0.05. The findings indicate that the Ecoliteracy and Adaptation (ELA) learning model based on local wisdom is more effective than Problem-Based Learning (PBL) in improving students’ learning interest. Contextual and experience-based learning through environmental and local wisdom integration encourages active participation, motivation, and students’ curiosity in the learning process.